Design of self-compensated rectifier with auxiliary circuit for radio frequency energy-harvesting applications - Zareianjahromi, Seyed Arash (2022)
Billion-plus devices will reportedly be connected to the internet via the "Internet of Things" (IoT). Most of these gadgets, including wireless sensors that are wirelessly connected to the internet, will not have a wired connection to the electrical grid and will instead rely on the energy stored in the batteries to operate themselves. Due to its lifespan and capacity constraints, the battery power source is a barrier to expanding a wireless sensor network to hundreds or millions of nodes. Energy harvesting is a practical method for powering at least specific wireless sensors and devices. Since RF energy harvesting is becoming more widely available, integrated, and compatible with wireless networks, it has become one of the most common energy scavenging technologies. Due to route loss, fast signal attenuation over distance, poor power efficiency of RF-DC converters, and restrictions restricting the highest allowable broadcast signal intensity, RF energy harvesting is severely constrained in its ability to capture large amounts of energy. Even if a matching network is utilized to minimize the input power losses received by the antenna and enhance the power transfer to the rectifier, transistors cannot function at the minimal power level required without an effective rectifier design. Enhancement of the efficiency of RF rectifiers and the reduction of the power consumption of the sensor circuitry and wireless transmitter necessary for the transmission of sensed data to a reader are both critical to enhancing the radio frequency energy harvester (RFEH) system’s overall power conversion energy (PCE). Due to distance and other considerations such as the unavailability of precise and consistent power; consequently, the RF rectifier's design will need to be able to handle a broad range of input power with acceptable efficiency. This work presents a five-stage self-compensated charge pump rectifier in 4 different implementations with the application of the diode-connected MOS transistors technique to decrease the leakage current and the threshold voltage in reverse and forward operation regions respectively with the objectives to achieve high PCE dynamic range above 20% and 1V sensitivity by generating optimal compensation voltage using auxiliary circuit. Each of these implementations has a unique auxiliary circuit that is designed to generate an optimal compensation voltage for each transistor in the main charge pump path, to convert RF signals to DC voltage efficiently. In comparison to conventional threshold voltage compensation circuits, where the level of compensation is restricted by the circuit construction and changes with input power, the proposed implementation achieves greater dynamic PCE throughout a wide input power range. This work is conceived and executed in a 130nm CMOS Silterra technology and obtained a broad range of 15 dBm with an efficiency of more than 20% and a sensitivity of -21 dBm for 1V output and a maximum PCE of 39.9% at -9 dBm of input power while driving a 1 MΩ load at 920 MHz.